2019
DOI: 10.3389/fnins.2019.01222
|View full text |Cite
|
Sign up to set email alerts
|

An Age-Adjusted EEG Source Classifier Accurately Detects School-Aged Barbadian Children That Had Protein Energy Malnutrition in the First Year of Life

Abstract: We have identified an electroencephalographic (EEG) based statistical classifier that correctly distinguishes children with histories of Protein Energy Malnutrition (PEM) in the first year of life from healthy controls with 0.82% accuracy (area under the ROC curve). Our previous study achieved similar accuracy but was based on scalp quantitative EEG features that precluded anatomical interpretation. We have now employed BC-VARETA, a novel high-resolution EEG source imaging method with minimal leakage and maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Our work confirmed that a large part of the variance of traditional and HR DPs depends on frequency and age, underscoring the need for frequency and age-dependent norms to detect BDD. This fixed-effect dependency has been reported many times for traditional log-spectra, including several papers from our group (Taboada-Crispi et al, 2018; Bosch-Bayard et al, 2001; Bringas Vega et al, 2019). Indeed, the shape of the norms or “developmental surfaces” for traditional measures hold up with the larger multinational sample.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Our work confirmed that a large part of the variance of traditional and HR DPs depends on frequency and age, underscoring the need for frequency and age-dependent norms to detect BDD. This fixed-effect dependency has been reported many times for traditional log-spectra, including several papers from our group (Taboada-Crispi et al, 2018; Bosch-Bayard et al, 2001; Bringas Vega et al, 2019). Indeed, the shape of the norms or “developmental surfaces” for traditional measures hold up with the larger multinational sample.…”
Section: Discussionsupporting
confidence: 66%
“…To check the validity of our new harmonized qEEG norms, revisited the problem of using the qEEG to classify school-children who suffered from Protein Energy Malnutrition limited to the first year of life (BMal) and to distinguish them from healthy classmate controls (BCtrl), who were matched by age, sex and handedness. Prior work is described in Bringas Vega et al (2019) Taboada-Crispi et al (2018). This work is part of the Barbados Nutrition Study-- a project that is still ongoing for nearly half a century (Galler et al, 1983a, 1983b).…”
Section: Validation Of the Harmmnqeeg Norms For Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…• To calibrate and test new methods for source localization of activation and connectivity as in He et al (2019). • As the basis for the construction of classification models to predict abnormal EEG activity as in Bringas Vega et al (2019).…”
Section: Projected Uses Of This Normative Datasetmentioning
confidence: 99%